Mapping Research on the Use of Algorithms in Commerce: A Bibliometric Analysis Based on Scopus - Ahmad Bilal Almagribi; Fikky Ardianto; Anas Taufan; Domy Kristomo (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2025)
Algorithms had garnered widespread attention across various scientific disciplines, including the commercial sector. According to data from Scopus, over 600 documents exploring the application of algorithms in commerce were identified. However, no comprehensive bibliometric analysis had been conducted to deeply examine the implementation of algorithms within this sector. This research aimed to fill this gap by analyzing the contributions of authors, affiliations, countries, and journals within the literature on commercial algorithms. Employing bibliometric methods on 645 Scopus-indexed documents, this study revealed that 2022 marked the peak of publications with 112 documents, indicating significant growth in this area. Li, Y. from Wuhan College, China, was recognized as the most productive author. Additionally, several universities in China were noted as the most productive affiliations. The ACM International Conference Proceeding Series was the most prolific source on this topic. The study also identified Computer Science, Engineering, and Mathematics as the most popular subject areas. These results indicate a need for further research into aspects such as data privacy, User Experience (UX), Dynamic Pricing Algorithms, and blockchain technology to enhance efficiency and security in commercial applications. This research paves the way for a broader understanding of algorithm utilization in commerce and provides recommendations for future studies.